Pequeno catálogo de ficções : seguido de "O Borges de Piglia e outros Borges - um ensaio" e "As perguntas que eu mesmo me fiz - um ensaio à maneira de Umberto Eco" - Bassi, Rafael José (2020)
In this dissertation, we present three joint works: two essays and a short tales’ book. The first essay, entitled “The Borges of Piglia and others Borges”, outlines a series of readings by different authors on the work of Jorge Luis Borges. Among them are: J. M. Coetzee, Susan Sontag, Roberto González Echevarría, Italo Calvino, Umberto Eco and, mainly, Ricardo Piglia. The second essay, whose title is “The questions I asked myself - an essay in the manner of Umberto Eco”, recalls the process of creating the storybook, which is finally presented in the third part, and which is entitled Little catalog of fictions. In this meeting of short narratives, we tried to work on plots with which to use the narrative techniques presented by the theories about the short tale.